Casebook on Contract Law - Poole, Jill (Oxford University Press, 2016)
Casebook on Contract Law provides students with a comprehensive selection of case law, addressing all aspects of the subject encountered on undergraduate courses. Extracts have been carefully chosen from a wide range of historical and contemporary cases to illustrate the reasoning processes of the courts, and to show how legal principles develop. Cases can either be analysed and discussed in isolation or, taken as a whole, the selection of cases form chapters providing a structured overview of the modern law of contract.